2011
DOI: 10.1371/journal.pone.0027356
|View full text |Cite
|
Sign up to set email alerts
|

Serum Fatty Acid-Binding Protein 4 Is a Predictor of Cardiovascular Events in End-Stage Renal Disease

Abstract: BackgroundFatty acid-binding protein 4 (FABP4/A-FABP/aP2), a lipid chaperone, is expressed in both adipocytes and macrophages. Recent studies have shown that FABP4 is secreted from adipocytes and that FABP4 level is associated with obesity, insulin resistance, and atherosclerosis. However, little is known about the impact of FABP4 concentrations on prognosis. We tested the hypothesis that FABP4 level predicts prognosis of patients with end-stage renal disease (ESRD), a group at high risk for atherosclerosis-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 23 publications
8
79
0
2
Order By: Relevance
“…The serum FABP4 level has also been reported to predict long-term cardiovascular events. [16][17][18] Reduction of the FABP4 level would be a novel therapeutic strategy for preventing the development of atherosclerosis and reducing the incidence of atherosclerotic cardiovascular disease. However, it is unclear whether FABP4 acts by an intracellular signaling mechanism via unidentified receptors, though it is a potential adipokine, an adipocyte-derived bioactive molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The serum FABP4 level has also been reported to predict long-term cardiovascular events. [16][17][18] Reduction of the FABP4 level would be a novel therapeutic strategy for preventing the development of atherosclerosis and reducing the incidence of atherosclerotic cardiovascular disease. However, it is unclear whether FABP4 acts by an intracellular signaling mechanism via unidentified receptors, though it is a potential adipokine, an adipocyte-derived bioactive molecule.…”
Section: Discussionmentioning
confidence: 99%
“…For example, intrarenal CD36 has been identified as a novel mediator in renal diseases associated with proteinuria and renal dysfunction (35). The elevated level of serum/plasma/urinary Fabp4 is considered a predictor or biomarker for renal dysfunction in diabetes and cardiovascular diseases (23)(24)(25)(26)(27). Hence, we further hypothesized that these affected IUGR offspring fed with HFD would develop metabolic perturbations and kidney injury in adulthood that might be associated with alterations of both renal CD36 and Fabp4 gene expression.…”
Section: Articlesmentioning
confidence: 99%
“…Emerging evidence suggested that CD36 (19)(20)(21)(22) and Fabp4 (23)(24)(25)(26)(27) are highly implicated in the pathogenesis of HFDinduced cell damage. For example, intrarenal CD36 has been identified as a novel mediator in renal diseases associated with proteinuria and renal dysfunction (35).…”
Section: Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, elevated serum concentration of FABP4 has been shown to be associated with obesity, insulin resistance, type 2 diabetes mellitus, hypertension, cardiac dysfunction, renal dysfunction, dyslipidemia, atherosclerosis, and cardiovascular events ( 8,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). However, little is known about the modulation of serum FABP4 level by therapeutic drugs including antidiabetic agents except for thiazolidinedione ( 25 ).…”
Section: Western Blot Analysismentioning
confidence: 99%